It's in the Field of View!: Coronary Artery Analysis on Chest Computed Tomographic Angiography. Issue 3 (2nd February 2018) - Hecht, Harvey S.; Narula, Jagat; Leipsic, Jonathon
Abstract : Supplemental Digital Content is available in the text.